2010
DOI: 10.1111/j.1467-789x.2009.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss interventions in young people (18 to 25 year olds): a systematic review

Abstract: This systematic review assesses weight loss interventions in young adults (18-25 years), who are vulnerable to weight gain. This age group experience critical life course points (leaving home for higher studies or job, pregnancy, cohabitation) and develop/establish lifestyle and behavioural patterns making this an opportune intervention period. Medline, Embase, Cinahl, PsychINFO and Cochrane Library were searched (1980 to March 2008). All trials and cohort studies with control groups that assessed weight loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
147
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(153 citation statements)
references
References 34 publications
5
147
1
Order By: Relevance
“…Systematic reviews suggest that many health behaviour change (HBC) trials suffer from a moderate to high risk of bias (e.g. Oberjé, de Kinderen, Evers, van Woerkum, & de Bruin, 2013;Poobalan, Aucott, Precious, Crombie, & Smith, 2009); more so than, for example, drug trials (Crocetti, Amin, & Scherer, 2010). Moreover, risk-of-bias scores have been found to explain heterogeneity in effect sizes, especially in trials with subjective outcome measures (Savovic et al, 2012;Wood et al, 2008).…”
Section: Editorialmentioning
confidence: 99%
“…Systematic reviews suggest that many health behaviour change (HBC) trials suffer from a moderate to high risk of bias (e.g. Oberjé, de Kinderen, Evers, van Woerkum, & de Bruin, 2013;Poobalan, Aucott, Precious, Crombie, & Smith, 2009); more so than, for example, drug trials (Crocetti, Amin, & Scherer, 2010). Moreover, risk-of-bias scores have been found to explain heterogeneity in effect sizes, especially in trials with subjective outcome measures (Savovic et al, 2012;Wood et al, 2008).…”
Section: Editorialmentioning
confidence: 99%
“…A systematic review concluded that weight control and behavioral interventions could be successful ways to boost self-esteem and increase satisfaction with body areas too (Poobalan, Aucott, Precious, Crombie, Smith, 2010). Among behavioral interventions', besides a healthy lifestyle or cutting out unhealthy foods, we can include an increased number of adequate physical activities and spending more time outdoors in the natural environment (Pop, 2015 b).…”
Section: Figure 1 Bmi / Body Dissatisfaction Correlationmentioning
confidence: 99%
“…Interventions to prevent weight gain and obesity among young women have the potential to significantly impact health outcomes and reduce health-care costs at the population level. However, traditional behavioural approaches to weight control may be ineffective for young women, with research suggesting lower rates of recruitment and attendance, higher attrition and less successful weight-loss outcomes (10) Furthermore, recent systematic reviews of weight management interventions in young adults (11)(12)(13) , including young women specifically (14) , have found insufficient evidence to guide intervention design and delivery in this area. One review concluded that there appear to be preferences for intervention by gender (13) .…”
mentioning
confidence: 99%
“…However, traditional behavioural approaches to weight control may be ineffective for young women, with research suggesting lower rates of recruitment and attendance, higher attrition and less successful weight-loss outcomes (10) Furthermore, recent systematic reviews of weight management interventions in young adults (11)(12)(13) , including young women specifically (14) , have found insufficient evidence to guide intervention design and delivery in this area. One review concluded that there appear to be preferences for intervention by gender (13) . Therefore in order to inform the design of interventions that are capable of engaging young adults, greater knowledge of the expectations of weight management programmes, motivations for weight loss, and barriers to and facilitators of behaviour change for each gender is required.…”
mentioning
confidence: 99%